2001
DOI: 10.2136/sssaj2001.6541334x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Litter Decomposition and Nutrient Dynamics in Four Southern Forested Floodplain Communities

Abstract: ABSTRACT, and Iatt floodplains, respectively, and these differences appeared related to hydroperiod. Decay rates were comparable to rates reported in similar floodplain environments. Net mineralization of both N and P was observed after 100 wk, but both elements accumulated in litter mixtures periodically. Differences in hydroperiod were observed among the four floodplain communities and decomposition of and nutrient mineralization from litter among them appeared to be inversely related to the number and durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 44 publications
4
51
0
Order By: Relevance
“…This could be attributed to the presence of high levels of labile materials that are susceptible to microbial degradation during the initial phase of incubation and accumulation of recalcitrant substances in the later phases of incubation that are resistant to microbial breakdown. Baker et al (2001) and Jacob et al (2010) reported that litter decomposes faster at initial phase due to its good biochemical quality and slows down with time due to accumulation of recalcitrant compounds.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the presence of high levels of labile materials that are susceptible to microbial degradation during the initial phase of incubation and accumulation of recalcitrant substances in the later phases of incubation that are resistant to microbial breakdown. Baker et al (2001) and Jacob et al (2010) reported that litter decomposes faster at initial phase due to its good biochemical quality and slows down with time due to accumulation of recalcitrant compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves that were not intact and any material other than brookside alder leaves were discarded. To minimize differences in litter quality, each species was collected from only one area in a single wetland (Aerts & de Caluwe 1997;Baker III et al 2001;Fennessy et al 2008). All litter was air-dried for a minimum of one week before being weighed and bagged.…”
Section: Decomposition Proceduresmentioning
confidence: 99%
“…Total soil phosphorus is typically between 6 and 100 times more concentrated in tree islands than in surrounding marshes (Jayachandran et al 2004). Also, decomposition rates are generally higher within their more oxidized soils, resulting in increased nutrient availability for woody growth (Baker et al 2001). Hydroperiods in the Everglades are co-influenced by climatic drivers and operations of the South Florida Water Management District (SFWMD), which controls more than 2,500 km of canals and levees in addition to hundreds of water control structures.…”
Section: Study Sitementioning
confidence: 99%